2008
DOI: 10.1007/s12231-008-9028-5
|View full text |Cite
|
Sign up to set email alerts
|

Declining Wild Mushroom Recognition and Usage in Burkina Faso

Abstract: Declining Wild Mushroom Recognition and Usage in Burkina Faso. Ethnomycological investigation was carried out in Burkina Faso, West Africa, using standardized interviews focused on 40 representative mushroom species assembled in a traveling herbarium (photographs plus preserved specimens). A total of 540 informants from 18 localities representing three main ethnic groups-Mòosé, Bobo, and Gouin-were interviewed, though the bulk of those interviewed were Mòosé (or Mossi) from the more populous central region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 17 publications
2
39
0
5
Order By: Relevance
“…Therefore, they know and use more or less the same species. Other interview studies have shown gender and age differences, with men being more knowledgeable than women (Kristensen & Balslev 2003), women being more knowledgeable than men (Guissou et al 2008), differing views between men and women (Wezel & Haigis 2000), and old people being more knowledgeable than young people (Guissou et al 2008).…”
Section: Species Usementioning
confidence: 96%
“…Therefore, they know and use more or less the same species. Other interview studies have shown gender and age differences, with men being more knowledgeable than women (Kristensen & Balslev 2003), women being more knowledgeable than men (Guissou et al 2008), differing views between men and women (Wezel & Haigis 2000), and old people being more knowledgeable than young people (Guissou et al 2008).…”
Section: Species Usementioning
confidence: 96%
“…(Guissou 2005) and Phlebopus sudanicus and Chlorophyllum molybdites are two common wild mushrooms in Burkina Faso. An ethnomycological study through 5 ethnics groups showed that knowledge is actively disappearing from one generation to another (Guissou et al, 2008), mostly due to urbanization and modern schooling. Intoxications cases were not mentioned, but the notion of poisonous mushrooms clearly exists within local people (Guissou et al, 2008).…”
Section: Extract Yieldsmentioning
confidence: 99%
“…An ethnomycological study through 5 ethnics groups showed that knowledge is actively disappearing from one generation to another (Guissou et al, 2008), mostly due to urbanization and modern schooling. Intoxications cases were not mentioned, but the notion of poisonous mushrooms clearly exists within local people (Guissou et al, 2008). C. molybdites is a pantropical saprotrophic species that occurs predominantly along roadside and in man-made nitrogen-rich ecosystems .…”
Section: Extract Yieldsmentioning
confidence: 99%
See 2 more Smart Citations